2017
DOI: 10.1038/srep40895
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthesis of ZnO/PMMA nanocomposites for photocatalytic applications

Abstract: The incorporation of nanostructured photocatalysts in polymers is a strategic way to obtain novel water purification systems. This approach takes the advantages of: (1) the presence of nanostructured photocatalyst; (2) the flexibility of polymer; (3) the immobilization of photocatalyst, that avoids the recovery of the nanoparticles after the water treatment. Here we present ZnO-polymer nanocomposites with high photocatalytic performance and stability. Poly (methyl methacrylate) (PMMA) powders were coated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…The O1s peak at a binding energy of 532.4 eV was assigned to carbonyl oxygen of the methyl esters groups of PMMA and of the –COOH. The O1s at a binding energy of 533.5 eV corresponded to bridge oxygen atoms C–O–CH 3 of the methyl ester group of PMMA 39 . The fitting peak at around 531.2 eV was attributed to oxygen in OH groups which suggested that PMMA obtained on NLC surface via the OH–bond.…”
Section: Resultsmentioning
confidence: 99%
“…The O1s peak at a binding energy of 532.4 eV was assigned to carbonyl oxygen of the methyl esters groups of PMMA and of the –COOH. The O1s at a binding energy of 533.5 eV corresponded to bridge oxygen atoms C–O–CH 3 of the methyl ester group of PMMA 39 . The fitting peak at around 531.2 eV was attributed to oxygen in OH groups which suggested that PMMA obtained on NLC surface via the OH–bond.…”
Section: Resultsmentioning
confidence: 99%
“…) =1 2 (9) where β denotes the heating rate (5, 10, 20 K/min), I = 1...4 and j = 1…N. N represents the number of the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent past, many research studies have attempted to improve thermal stability and to design optimal end-use properties of PMMA by adding different fillers (organoclays, alumina, silica, titania, zinc oxide, zirconium oxide and iron oxide) into the low viscosity monomers [7][8][9]. Different effects of various inorganic additives on the thermal stability and degradation of PMMA were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide nanoparticles were also fixed on glass plates as a photocatalyst to remove Acid Red 88 dye in aqueous solution [20]. This strategic way reported that mixing the photocatalyst with polymer matrix gives a new technique in water purification with characteristic features like good photocatalytic activity, low cost in consuming of the catalyst and no need to recover the catalyst after water treatment [21].…”
Section: ■ Introductionmentioning
confidence: 99%